Stability Assessment of Gob Side Entry at the Steeply Inclined Mining Face - Zhongcheng Qin; Yongle Liu; Feng Zhang; Nan Liu (Applied Sciences)
This study aims to comprehensively analyze the stability of rock mass around the gob side driving roadway in a significant inclined mining face. By considering the geological parameters and engineering conditions of specific cases, we carefully explored many factors affecting the stability of the surrounding rock mass, such as the mechanical properties of rocks, formation inclination, and the existence of goaf. Based on this, we construct a numerical model for analyzing the stability of the rock mass around the gob side driving roadway. Subsequently, we made a detailed investigation of the stress distribution and the characteristics of the plastic zone. In addition, through the analysis of the destruction mode and stress distribution characteristics of the rock mass, we establish the appropriate width of the coal pillar and thus provide a scientific basis for the formulation of support countermeasures; finally, the support countermeasures proposed in this study have achieved remarkable results in practical application and verify the feasibility and practicability of the research method. This support scheme ensures the stability of the gob side entry over its service life. It is hoped that this scheme can be promoted in similar projects to help maintain mine safety.